Organizational change through individual empowerment applying social psychology in prisons and policing - Toch, Hans (American Psychological Association, 2014)
"How does meaningful change occur? What is the role of the psychologist in promoting change? These questions drive this incisive retrospective by social psychologist Hans Toch, who has spearheaded participatory change over the years among violence-prone police, disenfranchised corrections officers, and inmates dehumanized by the misapplication of psychology in Supermax segregation units. Approaching each circumstance as a unique challenge, Toch has centered his work on simple tenets: treat humans as human, ameliorate environmental harm, and promote democracy by teaching individuals how to stand up and participate in their lives. By highlighting the necessity of active participation among stakeholders, Toch has shown process in social psychology to be more important than product. He demonstrates that psychology is best practiced not in the ivory tower but in the real world, among real people, seeking real answers to seemingly intractable problems. Toch displays a tender appreciation for the subjective experiences of people caught in difficult situations. Filled with amusing anecdotes and the wisdom of experience, this book displays the best that a life in applied psychology has to offer: a commitment not to behavioral theories or institutions, but to people"--Publicity materials. (PsycINFO Database Record (c) 2014 APA, all rights reserved)